Epistemologi Pendidikan Islam Berbasis Wahyu: Analisis Tilāwah, Tazkiyah, Dan Ta‘Līm Al-Kitāb Wa Al-Ḥikmah Dalam Qs. Al-Baqarah Ayat 151 - Sulaiman; Ahsan Hakim (Jurnal Pendidikan Indonesia, 2026)
. Contemporary Islamic education faces epistemological challenges marked by the weakening integration of revelation, reason, and moral values within educational processes. This condition has contributed to the disorientation of educational goals, the dichotomy of knowledge, and moral decline among learners. This article aims to analyze the epistemology of Islamic education based on revelation by employing Qur’ān Surah al-Baqarah verse 151 as its primary conceptual foundation. This study adopts a qualitative approach through library research and thematic Qur’anic analysis (tafsīr mawḍū‘ī). The findings reveal that Surah al-Baqarah verse 151 represents a hierarchical and integrative epistemological framework of Islamic education through the concepts of tilāwah, tazkiyah, ta‘līm al-kitāb, and ta‘līm al-ḥikmah. Tilāwah functions as the initial epistemic process of engaging with revelation; tazkiyah serves as the ethical prerequisite for valid knowledge; ta‘līm al-kitāb represents the transmission of normative knowledge; and ta‘līm al-ḥikmah signifies the integration of reason and revelation in practical wisdom. This study affirms that the epistemology of Islamic education is not value-free but oriented toward the formation of knowledgeable and ethically grounded individuals. The article contributes to strengthening the theoretical foundation of Islamic educational epistemology and offers a holistic paradigm relevant to the development of contemporary Islamic education